The way west : a novel - Guthrie, A. B., Jr. (Alfred Bertram), 1901-1991 (Houghton Mifflin, 2002)
"An enormously entertaining classic, 'The way west' brings to life the adventure of western passage and the pioneer spirit. The sequel to 'The Big Sky', this celebrated novel charts a frontiersman's return to the untamed West in 1846. Dick Summers, as pilot of a wagon train, guides a group of settlers on the difficult journey from Missouri to Oregon" -- back cover.